Decentralisation of policies affecting forests and estate crops in Kutai Barat district, East Kalimantan - Casson, A. (Center for International Forestry Research, 2001)
This study examines the initial impacts of decentralisation of policy making and policies affecting forests and estate crops in the district of Kutai Barat, East Kalimantan. Field work was conducted in mid 2000 and the author relied on secondary material and key informants to up date some information. Kutai Barat was formed through the partition of the original Kutai district shortly after the Habibie government issued Laws 22 and 25 in May 1999 on the decentralisation of authority from the central government to provincial and district governments. As a newly formed district, Kutai Barat has limited infrastructure and revenue. Local government officials also have limited capacity to develop policy and sustainably manage natural resources. However, decentralisation does provide opportunities for the government of Kutai Barat to secure a greater portion of the revenues generated by forests and mineral resources extracted within the district, and to build up the district's physical infrastructure and industrial facilities. During 2000, the Kutai Barat district government issued large numbers of small-scale timber extraction licenses, known as HPHH permits, to establish a district regulatory regime for forest exploitation. The district government also indicated that it would seek to encourage investors in the oil palm industry to establish operations in Kutai Barat. However, these plans have been undermined by continuing problems with PT London Sumatra, the district's largest estate crop investor. Social conflict resulting from large-scale mining operations at the PT KEM site is also presenting problems for the newly formed district.